Diffusion of muonic hydrogen in hydrogen gas and the measurement of the 1s hyperfine splitting of muonic hydrogen - Nuber, Jonas (2023)
The CREMA collaboration is pursuing a measurement of the ground-state hyperfine splitting (HFS) in muonic hydrogen (μp) with 1 ppm accuracy by means of pulsed laser spectroscopy. In the proposed experiment, the μp atom is excited by a laser pulse from the singlet to the triplet hyperfine sub-levels, and is quenched back to the singlet state by an inelastic collision with a H2 molecule. The resulting increase of kinetic energy after this cycle modifies the μp atom diffusion in the hydrogen gas and the arrival time of the μp atoms at the target walls. This laser-induced modification of the arrival times is used to expose the atomic transition. In this paper we present the simulation of the μp diffusion in the H2 gas which is at the core of the experimental scheme. These simulations have been implemented with the Geant4 framework by introducing various low-energy processes including the motion of the H2 molecules, i.e. the effects related with the hydrogen target temperature. The simulations have been used to optimize the hydrogen target parameters (pressure, temperatures and thickness) and to estimate signal and background rates. These rates allow to estimate the maximum time needed to find the resonance and the statistical accuracy of the spectroscopy experiment.